The influence of Arabic medicine on surgery in the Low Countries1. Issue 1 (2nd January 2020) - Van Hee, Robrecht
Abstract: The influence of Arab Medicine on Western science has recently been challenged. Using the example of two Flemish surgeons, Jan Yperman in the early 14th and Thomas Fijens in the late 16th century, this article argues that Arab physicians and surgeons have imposed a long lasting influence on the surgical practitioners in the Low Countries.